The first experience of two-stage treatment of transsphincteric fistulas of rectum by means of fibrin sealant - S. A. Frolov; A. M. Kuzminov; V. Yu. Korolik; I. S. Bogormistrov; M. O. Chernozhukova; Sh. T. Minbayev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To improve the shortterm and longterm results of transsphincteric rectal fistulas treatment by patented twostage method that includes elimination of fistulous tract with the subsequent enzyme treatment of the wound channel and delayed sealing by twocomponent biological glue. Material and methods. The method of cryptogenic transsphincteric rectal fistulas treatment is proposed. The method is based on elimination of fistulous tract by resection of internal lining. This is followed by sealing of the wound channel by biological glue which provides hermetic sealing as well as indirect stimulation of tissue regeneration. Treatment results of the patient group that matched inclusion criteria were analyzed: straight fistulous tract, absence of inflammatory changes and severe fibrosis in the area of fistula internal orifice. Prospective nonrandomized study which included 14 patients with cryptogenic transsphincteric rectal fistulas was carried out. At prehospital stage patients underwent transrectal ultrasound, fistulography and physiological tests. Results. Surgical intervention was carried out under local anesthesia, duration averaged 16 min (12 to 26), no intraoperative morbidity was registered. Pain intensity in postoperative period was minimal. Relapse developed in three patients (21.4%) of the 2nd, 3rd and 5th month of followup. Two patients (66%) underwent repetitive surgery by similar technique followed by complete elimination of the signs of disease. In one case at the 3rd month of followup transrectal ultrasound revealed the signs of relapse combined to ischioanal fat tissue leak that was probably undiagnosed at initial operation; reoperation was carried out - segmented proctoplasty by mucosal and muscular rectal graft. Assessment of anal sphincter continence after carried out surgery revealed no disorders. Conclusion. Surgical treatment of cryptogenic transsphincteric rectal fistulas by twostage method including elimination of fistulous tract followed by wound channel enzyme treatment and sealing by twocomponent biological glue allows to achieve good clinical effect at strict indications and rectal sphincter sparing. Its lowinvasiveness and minimal tissue traumatization provides decrease in postoperative morbidity rate and decreases patient rehabilitation time. At repeated administration of this method the recurrence rate decreases to 6% at preservation of anal sphincter function. Strict patient selection with transsphincteric rectal fistulas and careful preoperative investigation allow to improve treatment results due to technical simplicity of the method as well as due to low complication rate both in early, and in remote periods.